Deceptively-altered visual feedback alters 4km cycling time trial performance in trained cyclists - Westbrooks, J.; Prichett, W.; Fisher, M.; Pritchett, K. (Journal of Science and Cycling, 2017)
Introduction The brain maintains a performance reserve capacity by regulating fuel utilization. One method of overriding the governor is the utilization of deception. The purpose of this study is to examine the effect of deceptively-modified feedback on time to completion during a laboratory based 4000m time trial.